Simulating Intermediate Crack Debonding on RC Beams Strengthened with Hybrid Methods - Shukri, Ahmad Azim; Shamsudin, Mohd Fazaulnizam; Ibrahim, Zainah; Alengaram, Ubagaram Johnson; Hashim, Huzaifa (Brazilian Association of Computational Mechanics, 2018)
The externally bonded (EB) and the near-surface mounted (NSM) are two well-known methods for strengthening reinforced concrete (RC) beams. Both methods are unfortunately prone to fail prematurely through debonding when the amount of strengthening reinforcement provided is high. In response to this, a hybrid method that combines the EB and NSM method was introduced. The method allows the amount of reinforcement needed for EB and NSM methods to be reduced; this, in theory, should lower the interfacial stresses, thus reducing the possibility of debonding failures. While debonding failure can be prevented, certain amounts of debonding would still occur through the interfacial crack (IC) debonding mechanism which can affect the strength and stiffness of hybrid strengthened beams even if it does not directly cause failure. This paper presents a method to simulate IC debonding of hybrid strengthened beams using the moment-rotation approach. The proposed method allows a better prediction of maximum load and stiffness of the beams. The method is also less dependent on empirical formulations compared to the commonly used moment-curvature approach; this allows the method to be applicable to all material and shape of hybrid strengthening reinforcement, assuming correct material models are used. The proposed method was then used to perform parametric studies; among the important findings is the length of IC debonding tend to increase when FRP sheet with higher elastic modulus is used, thus negating most of the benefit from the higher modulus.